A measure of marketing price transmission in the Red Onion Market of Sri Lanka - Mathusuthan, K.; Sooriyakumar, K. (International Journal of Environmental & Agriculture Research, 2017)
In the past there were several protectionist trade policies to safeguard the local onion production. This study examines their impact by means of nominal and effective protection rates and competiveness in resource utilization by competitiveness coefficient. There is a long-run co-integration relationship between the farm and the retail prices marketing margin resulting from this long-run relationship cause asymmetric short-run dynamic adjustments between the farm and the retail prices Welfare distribution among stakeholders is measured by classical welfare analysis. The analysis indicates that both big and red onion producers are noticeably protected by the trade policies and receive returns greater than they would get under a free market condition. Trade policies benefit consumers over producers. Gains to the nation are substantial.
Keywords: Sri Lanka; Red Onion market; Transmission rate; Onion production; Farm